Development of calcium silicate-based composites for load-bearing implants / Seyed Farid Seyed Shirazi - Seyed Shirazi, Seyed Farid (2015)
The essential requirements for successful bone repair and regeneration using synthetic-based hard tissues are: (i) mechanical stability; (ii) bioactivity; (iii) biodegradability and (iv) interconnectivity to allow for efficient migration of bone cell precursors and for the vascularization necessary for bone formation. In the case of large, critical-size bone defects, the synthetic materials currently available fall short of meeting the combined requirements for high porosity and interconnectivity while maintaining mechanical properties and bioactivity. Therefore, fabrication of a tissue that maintains architectural support throughout the duration of the healing phase under load-bearing conditions has been a huge challenge in the field. During the past 30 years, a variety of synthetic bone graft substitutes based on bioactive ceramics and glasses have become available, including bioglasses, hydroxyapatite (HA), calcium silicates (CS, CaSiO3) and biphasic calcium silicate (α/β-CS). A major drawback of currently available bioactive ceramics is inadequate mechanical properties (low strength, toughness and high brittleness) for load-bearing applications. One way to address this has been addition of biocompatible materials such as polymers and bioinert ceramics as the reinforcement agents to cover the weak points of bioactive ceramics while maintaining the shine points of biological properties. The aim of this thesis is to develop synthetic bioactive tissues for the repair and regeneration of large bone defects in load-bearing applications. Major advances have been achieved in this thesis through the development of materials with the right balance between material properties, implant architecture and bioactivity to satisfy the functional and regenerative requirements of bone. Fabrication of new biocomposites based on CS matrix and using appropriate synthesis strategies for doping CS with the cations can turn brittle and weak ceramics into tough, elastic and strong bone tissues for load-bearing applications. CS/Alumina composites sintered at 1250°C showed significant enhancement in hardness and fracture toughness compared to pure CS due to the presence of hardener agent as alumina. Moreover, Doping the CS structure with the cations can increase the mechanical properties while keeping or improving the biological characteristics. CS nanopowders doped with monovalent (Ag+) and pentavalent (Ta5+) cations showed an improvement in hardness and fracture toughness. However, hFOB cell proliferation was increased at each time point in higher concentration of Ta, the results showed no significant differences in proliferation in the presence or absence of higher amount of Ag in the CS structure. The new composites of CS/ poly(1.8-octanediol citrate) (POC) were developed with the aim of controlling the weight loss and improving the biological and mechanical properties for fixation device applications. The reports confirmed a very high improvement in mechanical strength and biological properties with incorporation of 40 wt% POC. In conclusion, the approach adapted in this thesis is the rational combination of many validated individual elements, which act synergistically to produce for the very first time biomaterials which can substitute for lost bone, both by allowing bone formation and in the meantime withstanding load. These newly developed ceramics have the potential to have a significant contribution in existing therapies to provide a superior clinical result.